Buried in shades of night contested voices, Indian captivity, and the legacy of King Philip's War - Stratton, Billy J., 1970- (University of Arizona Press, 2013)
"Billy J. Stratton's critical examination of Mary Rowlandson's 1682 publication, The Soveraignty and Goodness of God, reconsiders the role of the captivity narrative in American literary history and national identity. With pivotal new research into Puritan minister Increase Mather's influence on the narrative, Stratton calls for a reconsideration of past scholarly work on the genre"--Provided by publisher.